Маркування та гравірування за допомогою лазера - Корсун, Г. А. (ХНУРЕ, 2023)
Different processes for processing materials with laser modifications on the basis of any possible faster preparation of the final product were considered. All methods work on pulsed lasers. These methods do not use inks, pigments, powders, or anything like that. Such marking methods, with the help of lasers, have high quality and very good resolution of the mark, drawing, engraving.